Posttransplant maintenance therapy in multiple myeloma: the changing landscape - Sengsayadeth, S (Blood Cancer J, 2017)
Transplant-eligible patients with multiple myeloma (MM) now have extended survival after diagnosis owing to effective modern treatment strategies that include new agents in induction therapy, autologous stem cell transplant (ASCT), consolidation therapy and posttransplant maintenance therapy. Standard of care for newly diagnosed, fit patients includes ASCT and, often nowadays, posttransplant maintenance. Several large studies have shown the efficacy of maintenance with thalidomide, lenalidomide and bortezomib in the treatment scheme of MM with regards to prolonging progression-free survival and, to a lesser degree, overall survival. Herein we discuss the data currently available to support the use of maintenance therapy in patients after ASCT as well as the newer available agents that may be a part of its changing landscape in the years to come.